2007
DOI: 10.1373/clinchem.2006.079194
|View full text |Cite
|
Sign up to set email alerts
|

Protein Profiling of Microdissected Pancreas Carcinoma and Identification of HSP27 as a Potential Serum Marker

Abstract: Background:Patients with pancreatic adenocarcinomas have a poor prognosis because of late clinical manifestation and the tumor's aggressive nature. We used proteomic techniques to search for markers of pancreatic carcinoma. Methods: We performed protein profiling of microdissected cryostat sections of 9 pancreatic adenocarcinomas and 10 healthy pancreatic tissue samples using ProteinChip technology (surface-enhanced laser desorption/ ionization). We identified proteins by use of 2-dimensional gel electrophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 29 publications
2
64
2
Order By: Relevance
“…Circulating sHsp27 levels were significantly higher in patients with HCC than in healthy control subjects. Previous studies have reported elevated sHsp27 levels in patients with breast cancer (Fanelli et al 1998;Banerjee et al 2011), non-small cell lung cancer (Zimmermann et al 2012) and both pancreatic and gastric adenocarcinoma (Melle et al 2007;Huang et al 2010); however, this is the first report of a rise in circulating sHsp27 levels in patients with HCC.…”
Section: Discussionmentioning
confidence: 54%
“…Circulating sHsp27 levels were significantly higher in patients with HCC than in healthy control subjects. Previous studies have reported elevated sHsp27 levels in patients with breast cancer (Fanelli et al 1998;Banerjee et al 2011), non-small cell lung cancer (Zimmermann et al 2012) and both pancreatic and gastric adenocarcinoma (Melle et al 2007;Huang et al 2010); however, this is the first report of a rise in circulating sHsp27 levels in patients with HCC.…”
Section: Discussionmentioning
confidence: 54%
“…Besides these main chaperone functions, HSP27 has been associated with apoptosis and cell proliferation and differentiation (6,7). Additionally, HSP27 is over-expressed in many kinds of cancers, although its role in cancer remains unclear (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…63) DJ-1 is translocated from the cytoplasm to nucleus upon addition of a mitogen to the culture medium 26) and is translocated to mitochondria after oxidative stress. 64) Increased levels of DJ-1 expression have been observed in various cancer cells and tissues, including breast, 51,52) prostate, 65,66) lung, 67,68) and endometrial, 69,70) thyroid, 71,72) pancreas, [73][74][75][76] esophageal, 77) ovary, 78,79) cervical, 80) liver, 81) gastric, 82 57,90) and leukemia. 91,92) Secretion of DJ-1 into the serum or nipple fluid has been found in patients with breast cancer.…”
Section: Tumor Suppressor Mm-1 and Neurodegenerationmentioning
confidence: 99%